2010
DOI: 10.1111/j.1751-7893.2010.00164.x
|View full text |Cite
|
Sign up to set email alerts
|

Early signs and symptoms of psychosis among Palauan adolescents

Abstract: Findings are generally consistent with previous research on early indicators, though several unexpected findings suggest that results from this study may not be fully generalizable beyond this relatively isolated and culturally distinct Micronesian nation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 56 publications
(91 reference statements)
0
10
0
Order By: Relevance
“…Majority of the studies utilized a prospective cohort design, 18 , 37 , 41 43 , 47 , 48 , 51 , 53 , 54 , 59 76 followed by cross-sectional design, 36 , 38 , 39 , 45 , 46 , 52 , 55 , 77 91 with the least using a case control approach. 40 , 49 , 50 , 56 58 , 92 94…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Majority of the studies utilized a prospective cohort design, 18 , 37 , 41 43 , 47 , 48 , 51 , 53 , 54 , 59 76 followed by cross-sectional design, 36 , 38 , 39 , 45 , 46 , 52 , 55 , 77 91 with the least using a case control approach. 40 , 49 , 50 , 56 58 , 92 94…”
Section: Resultsmentioning
confidence: 99%
“…In some studies cannabis use was assessed by self-report with no use of validated instruments. 18 , 44 , 53 , 60 , 63 66 , 68 , 69 , 71 , 75 , 77 79 , 81 , 82 , 84 , 90 For studies which used validated instruments, the following tools were used: Detection of Alcohol and Drug Problems in Adolescents [DEP-ADO], 67 European adaptation of multidimensional assessment instrument for drug and alcohol dependence, 95 Composite International Diagnostic Schedule (CIDI); 38 , 45 , 70 , 72 74 , 89 , 96 Kiddie schedule for non-affective disorders and schizophrenia (KSADS-E); 40 , 41 , 61 , 83 , 93 , 94 Cannabis Experience Questionnaire; 49 51 , 57 , 58 , 76 Minnesota center for twin and family research self-report for substance use; 36 Structured clinical interviews for diagnostic and statistical manual for mental disorders fourth edition (SCID/DSM-IV); 37 , 46 , 62 , 80 Alcohol, Smoking and Substance involvement Screening tool (ASSIST); 55 , 56 , 97 Substance use questionnaire; 42 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results also indicated a high rate of FEP for individuals from Palau; several studies have already noted increased psychosis on the island of Palau (Hezel & Wylie, 1992; Madraisau et al, 2010; Myles‐Worsley et al, 1999). Moreover, Hammond et al (1983) found that 43% of patients with schizophrenia in Palau had their first psychotic episode while living abroad.…”
Section: Discussionmentioning
confidence: 68%